Pengaruh Pembelajaran Ilmu Tajwid Melalui Media Power Point Terhadap Kemampuan Membaca Al-Qur’an Siswa Pada Mata Pelajaran Al-Qur’an Hadits Di Kelas Viii Mts Hubbul Wathan Cilawu Garut - Fauziah, Hapsah; Lia, Lia (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The Qur'an is the main source for Muslims which serves as a guide for life in the world to achieve life in the hereafter. Because of this function, the effort to study and understand the Qur'an is a very important issue so that the messages contained in it can be accepted as well as implemented. In addition, it is an inherent belief among Muslims that the Qur'an is a miracle of the Prophet Muhammad Saw which is eternal and its teachings are universal. This study aims to describe the Effect of Learning Tajweed Science Through Power Point Media on Students' Reading Ability in Al-Qur'an Hadith Subjects. Quantitative methods are used in this study because the research results are presented in the form of statistical figures. The type of research chosen is descriptive correlative, which is research that aims to determine the effect or relationship between two or more variables. Used to study a specific population or sample. Data collection using research tools, statistical data analysis whose purpose is to test the hypothesis given. Based on the results of hypothesis testing, it is found that there is an effect of the influence of Tajweed Science Learning through Power Point Media on Students' Qur'an Reading Ability in Qur'an Hadith Subjects showing a significant influence, this is evidenced by the results of a correlation analysis of 46.77% which lies in the range of 0.40-0.50 and is included in the high category with a confidence level of 5%. Thus Ha is accepted and H0 is rejected.  Keywords: Tajweed Science, Ability to Read the Qur'an